Access, accountability, and the proliferation of psychological therapy: On the introduction of the IAPT initiative and the transformation of mental healthcare - Pickersgill, Martyn (Soc Stud Sci, 2019)
Psychological therapy today plays a key role in UK public mental health. In large part, this has been through the development of the (specifically English) Improving Access to Psychological Therapies (IAPT) programme. Through IAPT, millions of citizens have encountered interventions such as cognitive behaviour therapy, largely for the treatment of depression and anxiety. This article interrogates how this national response to problems of mental ill-health – and the problematization itself – was developed, accounted for, and sustained. By imbricating economic expertise with accounts of mental ill-health and mechanisms of treatment, IAPT has revivified psychological framings of pathology and therapy. However, it has done so in ways that are more familiar within biomedical contexts (e.g. through recourse to randomized controlled trial studies). Today, the initiative is a principal player in relation to which other services are increasingly developed. Indeed, in many respects IAPT has transformed from content to context within UK public mental health (in a process of what I term ‘contextification’). By documenting these developments, this paper contributes to re-centring questions about the place and role of psychology in contemporary healthcare. Doing so helps to complicate assumptions about the dominance of linear forms of (de)biomedicalization in health-systems.